The Russian connection: new attacks and arrests. Issue 4 (April 2017) - Unknown
Abstract : As the controversy over whether Russian hackers played a role in the US elections staggers on, further allegations have been made about possible Kremlin-backed attacks. And arrests have been made in connection with some earlier incidents.